PENJABARAN NILAI NILAI PANCASILA DALAM PELAKSANAAN PEMILIHAN KEPALA DESA - Samosir, Aquilera Miranda (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Indonesia is a democratic country which means that all its citizens have the same right to vote and village head elections as a means of realizing democracy. This article was conducted with the aim that we describe and find out how the implementation or elaboration of Pancasila values, especially in the implementation of village head elections. The method used in this research is qualitative. Qualitative research is intended to understand the meaning or seek the meaning of events and their connections with ordinary people in certain situations. Basically the power of a democratic country is in the hands of the people for the common good. In Indonesia, the implementation of democracy is based on the Fourth Precept of Pancasila which reads